Synthesis of 1-Carboxamide-1,4-dihydropyridazines via Recyclization of Hydroxypyrrolines with Semicarbazides - Shabalin, Dmitrii A.; Ivanova, Evgeniya E.; Kuzmin, Anton V.; Dvorko, Marina Yu.; Schmidt, Elena Yu.; Trofimov, Boris A. (Synthesis, 2018)
Recyclization of available 5-hydroxypyrrolines with semicarbazide and its analogues has been studied. As a result, rare 1,4-dihydropyridazines with carboxamide function at the N-1 atom have been synthesized in up to 88% isolated yields.
Keywords: dihydropyridazine; semicarbazide; hydroxypyrroline; carboxamide; DFT studies